Tinjauan Teori POAC terhadap Perencanaan Siswa dalam Upaya Stabilitas Mutu Lulusan di SMAN 2 Pekalongan - Kistanti Kistanti; Mutammam Mutammam (ARZUSIN, 2026)
Student planning is an important aspect in maintaining the stability of graduate quality, yet studies that specifically discuss the application of the POAC management functions in student planning for quality stability remain limited. This study aims to analyze the application of the POAC management functions, which include planning, organizing, implementation, and controlling, in the student planning process. This study used a qualitative approach with an interview design, involving two informants selected through an informant selection technique. Data were collected through interviews and analyzed using content analysis techniques. The results showed that strategic student affairs planning was carried out in a structured manner through annual work meetings based on evaluations of previous graduates and government regulations. The school established graduate quality parameters focusing on academic score standards and designed a double-track program that had not yet been implemented to improve students’ work readiness. In addition, the potential of new students was mapped using the RIASEC model to ensure appropriate major placement. Quality stability was also maintained through a clear division of tasks among the school team, moral development, regular monitoring, and routine evaluation every semester. The conclusion of this study affirms that the structured integration of the POAC management functions plays an important role in supporting the stability of graduate quality. These findings contribute to the development of the literature on quality-based student management and provide practical implications for educational institutions in designing curriculum enrichment programs and building a synergistic distribution of roles within the school team.